Interferon gamma (IFN-γ)-mediated inflammation and the kynurenine pathway in relation to risk of hip fractures: the Hordaland Health Study - Apalset, E. M.; Gjesdal, C. G.; Ueland, P. M.; Øyen, J.; Meyer, K.; Midttun, Ø.; Eide, G. E.; Tell, G. S. (Osteoporosis international, 2014)
Summary The cytokine interferon gamma (IFN-γ) stimulates neopterin release and tryptophan degradation into kynurenines through the kynurenine pathway. High levels of neopterin were associated with increased hip fracture risk, as were some of the kynurenines, suggesting a role of IFN-γ-mediated inflammation in the processes leading to hip fracture. Introduction Low-grade systemic inflammation has been associated with bone loss and risk of fractures. Interferon gamma (IFN-γ) initiates macrophage release of neopterin and also stimulates degradation of tryptophan along the kynurenine pathway as part of cell-mediated immune activation. Plasma neopterin and the kynurenine/tryptophan ratio (KTR) are thus markers of IFN-γ-mediated inflammation. Risk of hip fracture was investigated in relation to markers of inflammation and metabolites in the kynurenine pathway (kynurenines). Methods Participants (71 to74 years, N = 3,311) in the community-based Hordaland Health Study (HUSK) were followed for hip fractures from enrolment (1998–2000) until 31 December 2009. Plasma C-reactive protein (CRP), neopterin, KTR, and six kynurenines were investigated as predictors of hip fracture, using Cox proportional hazards regression analyses. Results A hazard ratio (HR) of 1.9 (95 % confidence interval (CI) 1.3–2.7) for hip fracture was found in the highest compared to the lowest quartile of neopterin ( p trend across quartiles <0.001). CRP and KTR were not related to hip fracture risk. Among the kynurenines, a higher risk of fracture was found in the highest compared to the lowest quartiles of anthranilic acid and 3-hydroxykynurenine. For subjects in the highest quartiles of neopterin, CRP, and KTR compared to those in no top quartiles, HR was 2.5 (95 % CI 1.6–4.0). Conclusions This may indicate a role for low-grade immune activation in the pathogenic processes leading to hip fracture.